Variant of the mathematical economic order quantity inventory model (CEP) considering seasonality demand - Vicencio Checco, Gerald Antony (2023)
This research develops a mathematical model, a variant of the Economic Order Quantity (CEP) model based on historical demand information for products with a seasonal trend. The purpose is to calculate parameters of time and size of orders, so that these forecasts reduce costs and satisfy the estimated demand without entailing unnecessary expenses. The proposed model initially designs orders based on the forecast of future demand based on historical demand information with a seasonal trend (smoothed using the method of seasonal multipliers), then the forecast periods are grouped favorably (based on demand peaks), establishes logistical constants and analyzes the requirements in each group using restrictions that allow the volume of orders to be evaluated iteratively; Four analysis tests were carried out in different scenarios, redefining the logic of the restrictions. The results presented a mathematical model that is developed through iteration processes based on the established restrictions, concluding that with the developed model it is possible to determine the volume and the optimal periods to make these orders based on the seasonality of the demand.